2005
DOI: 10.1161/01.atv.0000150651.85907.69
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cellular Adenosine Uptake Limits Adenosine Receptor Stimulation in Patients With Hyperhomocysteinemia

Abstract: Objective-Endogenous adenosine has several cardioprotective effects. We postulate that in patients with hyperhomocysteinemia increased intracellular formation of S-adenosylhomocysteine decreases free intracellular adenosine. Subsequently, facilitated diffusion of extracellular adenosine into cells through dipyridamole-sensitive transporters is enhanced, limiting adenosine receptor stimulation. We tested this hypothesis in patients with classical homocystinuria (nϭ9, plasma homocysteine 93.1Ϯ24.7 mol/L) and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…44,45 This decreased activity of ENT1 elicits adenosine signaling by ARs as previously described, using inhibitors of ENT1 activity or in ENT1 À / À mice. 10,19,20 Interestingly, a correlation between ENT1 decreased activity with epithelium mesenchymal transition (EMT) of renal proximal tubule epithelial cells in vitro, was recently demonstrated. 46 EMT is a requisite for progression of tubule-interstitial fibrosis in the diabetic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 This decreased activity of ENT1 elicits adenosine signaling by ARs as previously described, using inhibitors of ENT1 activity or in ENT1 À / À mice. 10,19,20 Interestingly, a correlation between ENT1 decreased activity with epithelium mesenchymal transition (EMT) of renal proximal tubule epithelial cells in vitro, was recently demonstrated. 46 EMT is a requisite for progression of tubule-interstitial fibrosis in the diabetic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…14 It has been described that the equilibrative nucleoside transporters (ENTs), characterized by its sodium-independent facilitative transport activity, could have a major contribution on adenosine availability for signaling through adenosine receptor (AR). [15][16][17][18][19][20][21] ENTs activity mediates adenosine uptake to be either metabolized intracellularly, or to accumulate outside when the uptake activity is reduced. We have previously determined that the ENT1's activity decreased in diabetic rats' glomeruli 22 therefore, the handling of the nucleoside could be altered in this pathologic condition.…”
mentioning
confidence: 99%
“…Our previous reports have demonstrated that the combination of homocysteine and adenosine exacerbated TNF cytotoxicity and apoptosis in endothelial cells (7,8). This connection between homocysteine and adenosine has been associated with their active involvements in methionine metabolism and cellular methylation, as well as the enhanced cellular uptake of adenosine induced by homocysteine (13). To the best of our knowledge, there is a lack of studies evaluating the potential use of nucleoside transport inhibitors to block cellular adenosine uptake in vascular complications associated with homocysteine.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that a high level of homocysteine induces the synthesis of S-adenosylhomocysteine using the intracellular adenosine pool. This creates a transmembranous adenosine gradient and subsequently, facilitates the cellular uptake of extracellular adenosine (5,13). Dipyridamole is a clinical anti-platelet drug approved for the prevention of thromboembolism, and secondary prevention of ischaemic stroke and transient ischaemic attack.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular adenosine availability in body compartments is regulated by the capability of cells to uptake adenosine to be metabolized, accumulating extracellularly when uptake is decreased [11][12][13][14][15][16]. The uptake of adenosine by mammalian cells is mediated by the activities of the equilibrative (ENTs, Na + -independent) and the concentrative (CNTs, Na + -dependent) nucleoside transporters [17].…”
Section: Introductionmentioning
confidence: 99%